DINAMIKA KOLABORASI DALAM PENGEMBANGAN PARIWISATA KOTA KREATIF GASTRONOMI DI KOTA SALATIGA - Shafa Elmira Aziza; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
The City of Salatiga has strong potential in gastronomic tourism, reflected in its nomination for the UNESCO Creative Cities Network under the Creative City of Gastronomy category. Its development is guided by the 2021–2026 RIPPARDA and involves multi-actor collaboration among government, academia, communities, media, financial institutions, and businesses. However, collaboration dynamics remain suboptimal, hindering the realization of this goal. This study aims to analyze collaboration dynamics and identify driving and inhibiting factors in gastronomic tourism development. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation. The study applies Collaborative Governance theory by Kirk Emerson, Tina Nabatchi, and Stephen Balogh (2012), focusing on principled engagement, shared motivation, and capacity for joint action. Findings show that collaboration is constrained by weak communication, top-down approaches, and limited trust and commitment. Key barriers include unequal resources, hierarchical institutional structures, and political changes, while cultural flexibility acts as a supporting factor. The study recommends strengthening inclusive communication, shared commitment, resource allocation, accountability systems, and coordination mechanisms to improve sustainable collaboration.